Leadership Transformational Dan Komitmen Organisasional Terhadap Prestasi Peserta Pada Balai Pelatihan Vokasi Dan Produktivitas (Bpvp) Padang Kementerian Ketenagakerjaan Ri - Muhammad Taufik (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to investigate the relationship between transformational leadership, organizational commitment, and participant achievement at the Padang Vocational and Productivity Training Center (BPVP) under the Ministry of Manpower. This research uses a quantitative approach by distributing questionnaires to training participants at BPVP Padang. The research sample consisted of training participants who were active when the research was conducted. Data analysis was carried out using descriptive statistical methods and multiple regression. The findings of this study indicate that transformational leadership has a significant positive relationship with organizational commitment and participant achievement. Apart from that, organizational commitment also has a significant positive influence on participant achievement. The managerial implications of this research highlight the importance of developing transformational leadership and strengthening organizational commitment at BPVP Padang to increase the achievement of training participants.